Implementasi Program Pengendalian Penyakit Demam Berdarah Dengue (P2DBD) di Wilayah Kota Medan - Rapotan Hasibuan; Sri Suwitri; Sutopo Patria Jati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
An incidence rate (IR) and a case fatality rate (CFR) of Dengue Haemorrhagic Fever (DHF) in Medan City tended to increase since 2012. This might be due to a problem in implementing DHF Disease Control Program (P2DBD). The aim of this study was to analyse the influence of factors of communication, attitude, health centres’ characteristics, understanding of a standard and a target, resource, and environment towards the success of the P2DBD implementation program in Medan City. This was an observational study using a cross-sectional approach. Data were collected using a structured questionnaire and observation followed by conducting indepth interview for qualitative data. Number of respondents were 39 DHF officers working at all main health centres in Medan City. Furthermore, data were analysed using a technique of structural equation model (SEM) processed by a software of visual partial least square (VPLS). The results of this research showed that most of the respondents had very good communication (66.7%), positive attitude in supporting the program (82.1%), good characteristics of health centres (84.6%), good understanding of a standard and a target (66.7%), good resource (74.4%), conducive environment (76.9%), and good implementation of P2DBD (51.3%), a moderate level. Bivariate analysis demonstrated that communication and environment influenced the implementation. Furthermore, multivariate analysis showed that the implementation could be explained by the factors of communication, attitude, health centres’ characteristics, standard and target, resource, and environment equal to 67.4%. The R 2 value was included as a substantial category in which the most influenced factor was the environment. District Health Office needs to regularly conduct training of DHF case management, to supervise a program at health centres, and to initiate the existence of cadres for monitoring mosquito wrigglers. Health workers need to motivate, to persuasively ask a community, and to coordinate revitalisation of a DHF working group.